In what ways does placeness affect people’s behavior? Focusing on personal place attachment and public place image as connecting parameter - Dalavong, Phengsy; Im, Ha Na; Choi, Chang Gyu (Frontiers in Psychology, 2024)
Placeness is believed to play a significant role in enhancing the well-being and place-use of individuals, contributing profoundly to how spaces are experienced and interacted with. Despite its perceived importance, there is ongoing debate and insufficient clarity about how exactly placeness influences people’s behavior. This study aims to bridge this gap by theorizing and investigating the pathways from placeness to people’s behavioral intentions, emphasizing the roles of personal place attachment and public place image as pivotal mediators in this relationship. To explore these dynamics, we conducted a survey in Japan, examining the complex interplay between placeness and behavioral intentions, given their rich cultural heritage and modern urban pressures. We employed the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach for path analysis. The analysis suggests that placeness influences behavioral intention through personal place attachment. While placeness does affect public place image, this public image does not have an impact on behavioral intention. The results demonstrated that an individual’s activities, experiences, and cognition of a place are significant factors in creating the intention to engage in word-of-mouth, recommendation, and revisiting behaviors. Policymakers, urban planners, and designers need to understand how to foster people’s behavioral intentions when creating a place imbued with placeness.